2011
DOI: 10.1021/ja207218f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Lithium Enolate of 4-Fluoroacetophenone: Rapid-Injection NMR Study of Enolate Formation, Dynamics, and Aldol Reactivity

Abstract: Lithium enolates are widely used nucleophiles with a complicated and only partially understood solution chemistry. Deprotonation of 4-fluoroacetophenone in THF with lithium diisopropylamide occurs through direct reaction of the amide dimer to yield a mixed enolate-amide dimer (3), then an enolate homodimer (1-Li)(2), and finally an enolate tetramer (1-Li)(4), the equilibrium structure. Aldol reactions of both the metastable dimer and the stable tetramer of the enolate were investigated. Each reacted directly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 44 publications
0
46
1
Order By: Relevance
“…In the case of adding enolate 5 to cyclohexanone (Scheme 2), a rate law (eq 7) in conjunction with the assigned reactants as trisolvated dimers provided the generic mechanism involving a disolvated monomer intermediate (eqs 8 and 9). Despite speculation 34 and hard evidence 32 that the aldol addition occurs from aggregates, we found no support for aggregate-based Evans aldol additions. Of course, generalizing our results to other aldol additions is ill-advised.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…In the case of adding enolate 5 to cyclohexanone (Scheme 2), a rate law (eq 7) in conjunction with the assigned reactants as trisolvated dimers provided the generic mechanism involving a disolvated monomer intermediate (eqs 8 and 9). Despite speculation 34 and hard evidence 32 that the aldol addition occurs from aggregates, we found no support for aggregate-based Evans aldol additions. Of course, generalizing our results to other aldol additions is ill-advised.…”
Section: Discussioncontrasting
confidence: 94%
“…8,10,32 That is not to say, however, that deaggregation necessarily occurs before aldol addition. The results of our previous studies showed that enolization with LDA forms isomeric trisolvated dimers 2a/b , which are kinetically stable at −78 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of superstoichiometric lithium chloride provided optimal conversion and diastereoselectivity, which may be due to altered aggregation of the glycolate enolate or an increased degree of chelation during Michael addition. 30,31 …”
Section: Resultsmentioning
confidence: 99%
“…6 Most recently, Reich and coworkers have focused on measuring relative reactivities of aggregates and monomers under nonequilibrium conditions. 7 …”
Section: Introductionmentioning
confidence: 99%